A Discourse on the Malaysian Geographical Indications Act - Manique Cooray; Jia Chern Lee; Justin Johari Azman (Sriwijaya Law Review, 2023)
The Malaysian Parliament approved three Bills on Intellectual Property rights. One of it is the Geographical Indications Bill 2021, repealing the Geographical Indications Act 2000 (the Old Act). The new Bill received royal assent on 16 March 2022 and came into operation on 18 March 2022, known as the Geographical Indications Act 2022 (the New Act). The revisions made in the New Act were essential to harmonise intellectual property standards in Malaysia and facilitate the country’s accession to the Marrakesh Treaty. These amendments ensure that Malaysia adheres to the World Trade Organization’s Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) and fulfils its obligations under the Regional Comprehensive Economic Partnership (RCEP). The purpose of this paper is to examine the salient features introduced by the provisions of the New Act and to examine how the enhanced provisions attempt to realign intellectual property standards in Malaysia concerning Malaysia's broader obligations under the Regional Comprehensive Economic Partnership which have come into effect in Malaysia on 18 March 2022. The methodology employed in this research is doctrinal, especially focusing on the interpretation and analysis of the statutory provisions. In light of the changes in the New Act, New Regulations and the New Guidelines, the paper concludes by forwarding several recommended best practices to be considered by registered proprietors in the country.